Submerged membrane bioreactor for tenun dye wastewater treatment - Aina Hazuani, Hazman (2014)
The textile processing industry, from among the larger industrial consumers of water is a prime candidate for the development of intensive water recycling strategies and the recovery of valuable chemical products. Most studies have been directed towards the treatment of final effluent (end-of-pipe approach) in order to deal with the problems associated with textile waste water. New technologies, such as MBR, enable water reuse in combination with additional membrane filtrations, as a post treatment step. An important feature of MBR is the possibility of employing high sludge concentrations, facilitating the growth of specialised microorganisms, and promoting improved organic degradation. In this review, the characterisation of coloured wastewaters and the treatment methods are discussed, not only to enable water discharge but also its re-use. Parameters that need to be considered are COD, BOD, TSS, Colourization (ADMI) and MLSS. The results showed that the COD is decreased in the last 72 hours and increased in 96 hours. BOD results show that when the 24-hour period the value is decreased steadily until 96 hours in line with the increasing in time. TSS values decreased as the particles cannot pass through the filter as particles blocked during the refining process. Then MLSS increased due to the growth of microorganisms. Percentage of color removal was 26%, indicating that the MBR has the potential to emit particles in weaving dye wastewater. The data collected is used to improve the effectiveness of research looms dye using MBR.